Possibilities to recycle auto glass waste in building ceramics - Malaiškienė, Jurgita; Mačiulaitis, Romualdas; Mikalauskaitė, Raminta (Journal of Environmental Engineering and Landscape Management, 2014)
Substantial amounts of glass waste end up in landfills because unlike ordinary glass, auto glass is unsuitable for recycling in the glass industry due to organic additives. However, it was determined that the additives make auto glass waste appropriate for the production of building ceramics, which results in improved physical-mechanical and structural properties. The optimum quantity of the additive contained in auto glass waste amounts to 15% of the formation mixture, and the most appropriate burning temperature is 1080 °C. The density of such ceramic chip is 2059 kg/m3 , the water absorption determined after 72 h is 1.2%, and the forecasted frost resistance at the beginning of decomposition is 1343 cycles, but amounts to 2188 cycles at the end of decomposition.